A study on socio-demographic and obstetric profile, contraceptive use and reasons for medical termination of pregnancy among women attending medical termination of pregnancy clinic in Purba Medinipur district of West Bengal, India - Kulsum, Kaniz; Majumdar, Kunal Kanti (International Journal Of Community Medicine And Public Health, 2022)
Background: Induced abortion contributes significantly to maternal morbidity and mortality in developing countries yet women still seek repeat induced abortion in-spite of the availability of contraceptive services. The objective of this study was to identify the socio-demographic and obstetric profile of the mother’s seeking abortion as well as causes for seeking abortion. Methods: This is a cross-sectional study among selected women undergoing medical termination of pregnancy (MTP) at Tamluk district hospital and Haldia sub divisional hospital (SDH) of Purba Medinipur district, West Bengal. Results: A total of 52 women participated in the study. Among the study subjects, majority (53.83%) of the women were between 26-35 years of age. 88.46% of participants were Hindu by religion and belonged to nuclear families (80.76%). Common reasons given by the mothers for terminating of the pregnancy were previous baby too young (32.69%) and completed family size (28.84%) and contraceptive failure (28.84%). Conclusions: Unmet need of contraception is still an issue in respect to unwanted pregnancy. So focused attention from Front line workers like ANM, ASHA is required to meet the unmet need of contraception.